ON RADIAL DISTRIBUTION OF JULIA SETS OF SOLUTIONS TO COMPLEX DIFFERENTIAL EQUATIONS WITH MEROMORPHIC COEFFICIENTS - Zhang, Guowei (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper, we mainly investigate the radial distribution of Julia set of solutions to some second order complex linear diﬀerential equations with meromorphic coeﬃcients, and find out the lower bound of it. The radial distributions of Julia sets of derivatives of these solutions are also obtained.